Historiseringen av Kirunas kulturmiljö - i skenet av stadsomvandlingen - Simonsuuri, Olga (2016)
Uppsats för avläggande av filosofie kandidatexamen i Kulturvård, Bebyggelseantikvariskt program 15 hp Institutionen för kulturvård Göteborgs universitet 2015:32 The city of Kiruna in northern Sweden is in process of transformation as a consequence of the mining industry. Parts of the city centre has to be moved to a new location. Some parts of the built environment will be demolished, while some buildings assessing great cultural values has been selected and will be moved to the new location. The aim of this thesis is to explore how the built heritage of Kiruna has its own specific text-based infrastructure. Discursive practices over time plays a great role in what is actually being considered as part of the cities heritage. To examine this, different categories of operators that play a big role in the historicization of Kirunas has been analysed. This includes the municipality, operators in the tourism-industry, the Kiruna-based organization 'Kirunas Rötter', a scientist and also independent authors. The operators play different roles and operate through different types of publications which are valued equally in the analysis. The reason for this is to give a more democratic picture of what, over a long period of time, has been viewed as the heritage of Kiruna. Eight components has been distinguished from this analysis: The first built environment, The dream of the pattern-city, LKAB:s buildings and the social welfare, The SJ-area and its built environment, The church as a monument and Modern architecture. These components has been formed during a long period of time and are anchored in the minds of the inhabitants. The analysis also shows that the components play a great role in decisions that are made today regarding the transformation of the city. A question that is discussed in the end of the thesis is if there is any way that the image of Kirunas built environment and heritage could be made more nuanced?